Heroic diplomacy : Sadat, Kissinger, Carter, Begin and the quest for Arab-Israeli peace - Stein, Kenneth W., 1946- (New York : Routledge, 1999)
Heroic Diplomacy provides an unequalled insight into the internal divisions and untold stories of the peace process, covering an extraordinary range of first-hand accounts.
Book Cover; Title; Contents; Preface; Acknowledgments; The Key Players in Arab-Israeli Diplomacy 1973 1978; The Arab-Israeli Conflict 1947 1973; The October 1973 War; From War to Diplomacy The Kilometer 101 Talks; The 1973 Geneva Middle East Peace Conference and the Buildup to Sinai I; The Syrian-Israeli Agreement, Sinai I and II, and Defining a Comprehensive Peace 1974 1977; Unintended Consequences The 1977 Road to Geneva Ends in Jerusalem; From Jerusalem to Oslo and Beyond 1978 1998; Appendix; Notes; Works Cited and Suggested Reading; Index.
Includes bibliographical references (pages 313-320) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Arab-Israeli conflict -- 1973-1993.; Arab-Israeli conflict -- Diplomatic history; Diplomatic negotiations in international disputes; Arab countries -- Foreign relations -- Israel; Israel -- Foreign relations -- Arab countries; Israel-Arab War, 1973 -- Peace; Arab-Israeli conflict -- 1993- -- Peace; Conflit israélo-arabe -- 1973-1993.; Conflit israélo-arabe -- Histoire diplomatique; Négociations diplomatiques dans les conflits internationaux; États arabes -- Relations extérieures -- Israël.; Israël -- Relations extérieures -- États arabes; Guerre israélo-arabe, 1973 -- Paix; Conflit israélo-arabe -- 1993- -- Paix; HISTORY -- General; Peace; Arab-Israeli conflict; Arab-Israeli conflict -- Diplomatic history; Arab-Israeli conflict -- Peace; Diplomatic negotiations in international disputes; Diplomatic relations; Arab countries; Israel; Since 1973